Employee Performance Through Employee Engagement in Cargo Companies - Aswanti Setyawati; Cecep Pahrudin; Lira Agusinta; Rohana Sitanggang; Primadi Candra Susanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the influence of self-efficacy and discipline on employee performance, both directly and indirectly through employee engagement as a mediating variable, in cargo companies located in DKI Jakarta. A quantitative descriptive approach was applied, using purposive sampling with a total of 337 respondents. Data were analyzed using SmartPLS. The results show that both self-efficacy and discipline have a positive and significant impact on employee engagement and employee performance. Employee engagement also has a positive and significant effect on employee performance. Furthermore, self-efficacy positively influences employee performance through employee engagement, whereas discipline does not show a significant indirect effect through engagement. These findings offer practical implications for human resource management in the cargo sector to enhance employee performance by fostering self-efficacy and engagement. This study is limited to a specific geographical area and time frame, suggesting the need for broader future research. Keywords: Employee Performance, Employee Engagement, Self-Efficacy, Discipline